Asymmetric power and market failure: Power hazard in exchange - Korkut Alp Ertürk (The University of Utah, Department of Economics, 2016)
In simple textbook treatment of bilateral exchange traders end up on the contract curve such that the trading surplus is maximized regardless of any asymmetric bargaining power they might have. However, that need not be true when the terms of exchange are determined by uncooperative bargaining, for gains from trading will not reach its potential unless traders refrain from acting strategically. But, because power asymmetry creates quasi-rents that the more powerful player can capture, she might maximize her payoff when total gain from trading falls short of its potential. In other words, power asymmetry can make acting strategically tempting for the more powerful player, which however is socially costly. Using game theory the paper specifies profit maximizing strategic behavior under asymmetric power and considers its relevance for a more general conception of market exchange where traders bargain strategically. Two examples, involuntary unemployment and North's theory of the state, are then discussed in light of the model developed.
Keywords: A10; D70; C70; E02; 330; Asymmetric Power; Rent Seeking; Uncooperative Games; Strategic Bargaining